Critical determinants of mitochondria-associated neutral sphingomyelinase (MA-nSMase) for mitochondrial localization - Rajagopalan, Vinodh (Biochim Biophys Acta, 2014)
BACKGROUND: A novel murine mitochondria-associated neutral sphingomyelinase (MA-nSMase) has been recently cloned and partially characterized. The subcellular localization of the enzyme was found to be predominantly in mitochondria. In this work, the determinants of mitochondrial localization and its topology were investigated. METHODS: MA-nSMase mutants lacking consecutive regions and fusion proteins of GFP with truncated MA-nSMase regions were constructed and expressed in MCF-7 cells. Its localization was analyzed using confocal microscopy and sub-cellular fractionation methods. The sub-mitochondrial localization of MA-nSMase was determined using protease protection assay on isolated mitochondria. RESULTS: The results initially showed that a putative mitochondrial localization signal (MLS), homologous to an MLS in the zebra-fish mitochondrial SMase is not necessary for the mitochondrial localization of the murine MA-nSMase. Evidence is provided to the presence of two regions in MA-nSMase that are sufficient for mitochondrial localization: a signal sequence (amino acids 24–6) that is responsible for the mitochondrial localization and an additional 'signal-anchor' sequence (amino acids 77–99) that anchors the protein to the mitochondrial membrane. This protein is topologically located in the outer mitochondrial membrane where both the C and N-termini remain exposed to the cytosol. CONCLUSIONS: MA-nSMase is a membrane anchored protein with a MLS and a signal-anchor sequence at its N-terminal to localize it to the outer mitochondrial membrane. GENERAL SIGNIFICANCE: Mitochondrial sphingolipids have been reported to play a critical role in cellular viability. This study opens a new window to investigate their cellular functions, and to define novel therapeutic targets.